2018
DOI: 10.1075/fol.15010.wil
|View full text |Cite
|
Sign up to set email alerts
|

Flemish Sign Language development

Abstract: This case study provides a first exploratory study on the early Flemish Sign Language acquisition of a deaf infant from the perspective of Halliday’s Systemic Functional Theory. It highlights some remarkable aspects of sign language acquisition with respect to interpersonal interaction between the child and its mother. The free play interactions of the Deaf mother and her moderately deaf daughter were recorded when the child was 6, 9, 12, 18 and 24 months old. These interactions were annotated in ELAN and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The phenomenon of babbling, first observed around the age of 10 months, is not exclusive to speech, but a universal phenomenon in which vocal and manual babbling coexist, have the same function, and follow a similar course over time (Petitto & Marentette, 1991;Petitto, 1997;Masataka, 2000;Wille, Mouvet, Vermeerbergen, & Van Herreweghe, 2018). In addition, research has shown a clear developmental pattern within the manual parameters where more complex parameters are replaced by less complex ones (Morgan, 2014;Wille et al, 2018). The most accurate parameter is found to be location, followed closely by movement, whereas handshape is considered least error resistant.…”
Section: Sign Language Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of babbling, first observed around the age of 10 months, is not exclusive to speech, but a universal phenomenon in which vocal and manual babbling coexist, have the same function, and follow a similar course over time (Petitto & Marentette, 1991;Petitto, 1997;Masataka, 2000;Wille, Mouvet, Vermeerbergen, & Van Herreweghe, 2018). In addition, research has shown a clear developmental pattern within the manual parameters where more complex parameters are replaced by less complex ones (Morgan, 2014;Wille et al, 2018). The most accurate parameter is found to be location, followed closely by movement, whereas handshape is considered least error resistant.…”
Section: Sign Language Developmentmentioning
confidence: 99%
“…The most accurate parameter is found to be location, followed closely by movement, whereas handshape is considered least error resistant. This is especially visible when a marked handshape is replaced by an unmarked handshape (C, A, S, 1 or 5) (Boyes Braem, 1990;Mann, Marshall, Mason, & Morgan, 2010;Marentette & Mayberry, 2002;Wille et al, 2018). Unmarked handshapes tend to be more frequent and motorically and visually simpler than the marked handshapes.…”
Section: Sign Language Developmentmentioning
confidence: 99%